Revision of the Aggressiveness dimension of Dimensional Clinical Personality Inventory - Lucas de Francisco Carvalho (Psicologia: Teoria e Prática, 2015)
The present study aimed to review the Aggressiveness dimension of the Dimensional Clinical Personality Inventory (IDCP) in two steps: the first focused on developing new and the second for testing the psychometric properties in a sample of 230 subjects, 176 women, aged between 18 and 63 years, with minimum education of undergraduate (52.6%). The subjects answered the IDCP, the Revised NEO Personal-ity Inventory (NEO-PI-R) and the Personality Inventory for DSM-5 (PID-5). The first step resulted in 47 items, of which 20 were new. The second step resulted in a com-posite of 16 items, in two interpretable structure components, antagonism and vio-lence, with internal consistency coefficients of .89 for total, and .82 for each compo-nent. The analysis of the scale with NEO-PI-R and PID-5 revealed consistent and expected correlations. The data reveal the adequacy of the new Aggressiveness dimen-sion of IDCP.